PERBANDINGAN EFISIENSI BIAYA PRODUKSI LISTRIK PER KWH ANTARA PENGGUNAAN B30 (BIO DIESEL+HSDF) DAN MFO : - - Joniarta, I Wayan; Muhamad Renaldi Setiawan, (Energy, Materials and Product Design, 2022)
Production cost analysis research was conducted to determine the comparison of production costs produced by fuel types B30 (Bio Diesel+HSDF) and MFO . So that the efficiency of the fuel can be known. Data on usage is taken from the daily report on the operation of the plant on December 31, 2021 at the Ampenan ULPLTD. From the data analysis, it was found that MFO fuel is more efficient than B30 (Bio Diesel+HSDF) fuel. Because to produce 1 kWh using B30 (Bio Diesel+HSDF) fuel requires a production cost of Rp. 4,144.29,- /kWh, while for 1 kWh MFO requires a production cost of Rp. 2,189,655,-/kWh. And specific Fuel Consumption ( SFC ) the fuel required by DO (B30+HSDF) fuel is 0.3166 Ltr/kWh producing a power of 1,143 kWh which is higher than the Specific Fuel Consumption at MFO of 0.18715 Ltr/kWh producing a power of 4974,785 kWh.